Complete chloroplast genomes of Saccharum spontaneum, Saccharum officinarum and Miscanthus floridulus (Panicoideae: Andropogoneae) reveal the plastid view on sugarcane origins. Issue 6 (1st November 2016) - Evans, Dyfed Lloyd; Joshi, Shailesh Vinay
Abstract : Sugarcane ( Saccharum hybrid cultivar) ranks among the world's top 10 food crops and annually provides 60–70% of the sugar produced worldwide. Despite its economic importance there has been no large-scale systematics study of genus Saccharum and the existing model of sugarcane origins has remained largely unchallenged for almost 50 years. For the first time, we have assembled the complete plastid genomes of Miscanthus floridulus (first report for this genus), Saccharum spontaneum and Saccharum officinarum allowing us to elucidate the phylogenetic origins of Saccharum s.s . species. We demonstrate that Saccharum s.s. is divided into four species, with S. spontaneum diverging from the remainder of the genus about 1.5 million years ago and S. robustum diverging 750, 000 years ago. Two separate lineages, one leading to S. officinarum and the other leading to modern hybrid cultivars diverged from S. robustum 640, 000 years ago. These findings overturn all previous hypotheses on sugarcane origins, demonstrating that sugarcane's antecedents could not have arisen by human action. All modern cultivars share a common Polynesian origin, whereas Old World canes, S. barberi and S. sinense, cluster as a distinct S. officinarum lineage. This makes modern cultivars a distinct species of genus Saccharum, and we formally propose the name Saccharum cultum for the ancestor of all lineages currently classified as Saccharum hybrid cultivars.